Implementation and evaluation of an educational programme to support registered nurses during clinical supervision of student nurses in medical and surgical wards in a training health facility, Namibia - Neshuku, Hanna; Justus, Amukugo Hans (International Journal of Advanced Nursing Studies, 2015)
The purpose of this paper is to provide an account of the implementation and evaluation of the educational programme was to support registered nurses in the Oshana region, Namibia educationally, in order to enable them to provide effective clinical supervision of student nurses The researcher selected to conduct a workshop because during a workshop it is possible to have two-way communication that encouraged the exchange of ideas and facts with the aim of sharing valued information among one another. The duration of the workshop was two days. The workshop was attended by registered nurses (registered nurses from a training institution and training health facilities) from the Oshana Region. Participants were selected using a criterion sampling method (registered nurses who were supervising second and third year nursing students during clinical practice; those registered nurses were from medical and surgical wards at training heath facilities in the Oshana Region and had been working there for a year or more). There were no limitations on the number / sample size; the researcher allowed all participants who turned up to attend the workshop resulted in seventeen participants attended the workshop. The programme was implemented in three phases which in turn was divided into sessions. The orientation phase provided an introduction to the workshop where aspects related to the purpose, goals, and objectives of the workshop and logistical arrangements of the implementation of the programme were discussed. The working phase consisted of three sessions which is corresponding to the programme objectives. The implementation of each session was based on the specific objective activities of that session and it was expected to produce an outcome that would help the registered nurses during the execution of their clinical supervisory duties of nursing students During the termination phase two qualitative evaluations were done firstly, the evaluation of the programme implementation for participants to describe their experiences from the programme activities. Secondary, post implementation evaluation or impact evaluation was done, two months after the implementation of the programme with the aim of assessing the long-term effects of the programme activities as might be signified by changes in the way of clinical supervision of student nurses was provided after the programme implementation.The results of the programme implementation evaluation indicated a strong feasibility for implementation as could be inferred from the successful implementation of the programme activities as planned and by the programme contentment with the context of implementation. The post evaluation outcome evaluation indicated that the participant find the programme worthwhile and demonstrated a positive attitudes towards the programme as they were satisfied with the programme tried to implement the knowledge gained during their routine activities and recommended the decentralization of the programme.